Analisis Tantangan Multidimensi dalam Pengelolaan Pendidikan Anak Usia Dini di Kabupaten Bone - R, Nurhasanah (Prodi PIAUD STAI AL-GAZALI BONE, 2025)
Early Childhood Education Institutions (PAUD) in Bone Regency, South Sulawesi, face complex challenges rooted in socio-economic, infrastructure, and cultural dynamics. This study investigates the multidimensional barriers that hinder the effective management of early childhood education through qualitative field studies. Key findings reveal chronic funding limitations, inadequate infrastructure, and uneven teacher training as key barriers. In addition, cultural perceptions that prioritize informal parenting at home over formal early childhood education programs exacerbate low participation rates, especially in rural areas. Geographical isolation further restricts access, while fragmented coordination between stakeholders hampers systemic improvement. The study highlights the intersection between structural inequalities and local practices, with the argument that sustainable solutions require contextual strategies that integrate financial investment, community engagement, and policy reform. By placing the challenges of Bone Regency in the global discourse on early childhood education in developing regions, this study provides empirical insights into the interaction between the global education framework and local realities. The recommendations emphasize collaborative governance, infrastructure priorities, and culturally sensitive advocacy to align early childhood education services with national standards and community needs.